1997
DOI: 10.1091/mbc.8.7.1343
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a recycling role for Rab7 in regulating a late step in endocytosis and in retention of lysosomal enzymes in Dictyostelium discoideum.

Abstract: The mammalian small molecular weight GTPase Rab7 (Ypt7 in yeast) has been implicated in regulating membrane traffic at postinternalization steps along the endosomal pathway. A cDNA encoding a protein 85% identical at the amino acid level to mammalian Rab7 has been cloned from Dictyostelium discoideum. Subcellular fractionation and immunofluorescence microscopy indicated that Rab7 was enriched in lysosomes, postlysosomes, and maturing phagosomes. Cell lines were generated that overexpressed Rab7 wild-type (WT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 65 publications
4
66
0
Order By: Relevance
“…Thus, beside homotypic fusion, syntaxin 7 could also mediate fusion of D. discoideum endosomes with vesicles carrying components necessary for their maturation, such as proteases and vacuolar ATPase. The existence of such vesicles in D. discoideum has already been suggested by the study of Rab7 mutants (48,49). Given the similarity between D. discoideum and professional phagocytes, it is likely that syntaxin 7 plays similar roles in the endo-phagosomes of mammalian phagocytes, organelles where homotypic as well as heterotypic fusions take place (50,51).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, beside homotypic fusion, syntaxin 7 could also mediate fusion of D. discoideum endosomes with vesicles carrying components necessary for their maturation, such as proteases and vacuolar ATPase. The existence of such vesicles in D. discoideum has already been suggested by the study of Rab7 mutants (48,49). Given the similarity between D. discoideum and professional phagocytes, it is likely that syntaxin 7 plays similar roles in the endo-phagosomes of mammalian phagocytes, organelles where homotypic as well as heterotypic fusions take place (50,51).…”
Section: Discussionmentioning
confidence: 89%
“…As Dictyostelium postlysosomes constitutively exocytose their contents, we speculate that the late phase of WASH and retromer activity provides a mechanism to retrieve hydrolases before they are lost by exocytosis. Indeed, the sequential delivery and retrieval of hydrolytic enzymes during phagosome maturation is well characterized (33) and a late hydrolase retrieval step was previously proposed by others (33,58), who showed that hydrolase retention is disrupted by dominant negative Rab7-a now well-characterized regulator of the retromer (59). One of the best characterized roles for the retromer is to facilitate acid hydrolase trafficking by driving the retrograde trafficking of the cation-independent mannose-6-phosphate receptor (CI-M6PR) from lysosomes back to the trans-Golgi network (TGN) (37).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, PI 3-kinases also play a role in regulating lysosome-and phagosome-homotypic fusion in Dictyostelium (Buczynski et al, 1997a;Rupper et al, 2001b), although in this latter case the product required appears to be phosphoinositide (3,4,5)-trisphosphate. PKB/Akt, in addition to the PI 3-kinases PIK1 and PIK2, regulates homotypic phagosome fusion in Dictyostelium (Rupper et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%